Continuous soil carbon storage of old permanent pastures in Amazonia. (14th December 2016) - Stahl, Clément; Fontaine, Sébastien; Klumpp, Katja; Picon‐Cochard, Catherine; Grise, Marcia Mascarenhas; Dezécache, Camille; Ponchant, Lise; Freycon, Vincent; Blanc, Lilian; Bonal, Damien; Burban, Benoit; Soussana, Jean‐François; et al.
Abstract: Amazonian forests continuously accumulate carbon (C) in biomass and in soil, representing a carbon sink of 0.42–0.65 GtC yr −1 . In recent decades, more than 15% of Amazonian forests have been converted into pastures, resulting in net C emissions ( 200 tC ha −1 ) due to biomass burning and litter mineralization in the first years after deforestation. However, little is known about the capacity of tropical pastures to restore a C sink. Our study shows in French Amazonia that the C storage observed in native forest can be partly restored in old (≥24 year) tropical pastures managed with a low stocking rate (±1 LSU ha −1 ) and without the use of fire since their establishment. A unique combination of a large chronosequence study and eddy covariance measurements showed that pastures stored between −1.27 ± 0.37 and −5.31 ± 2.08 tC ha −1 yr −1 while the nearby native forest stored −3.31 ± 0.44 tC ha −1 yr −1 . This carbon is mainly sequestered in the humus of deep soil layers (20–100 cm), whereas no C storage was observed in the 0‐ to 20‐cm layer. C storage in C4 tropical pasture is associated with the installation and development of C3 species, which increase either the input of N to the ecosystem or the C:N ratio of soil organic matter. Efforts to curb deforestation remain an obvious priority to preserve forest C stocks and biodiversity. However, our results show that if sustainable management is applied in tropical pastures coming from deforestation (avoiding fires and overgrazing, using a grazing rotation plan and a mixture of C3 and C4 species), they can ensure a continuous C storage, thereby adding to the current C sink of Amazonian forests. Abstract : We find that the old pastures (≥24 years) have a high C storage, explained by a large part of C3 originated by legumes and shrubs and the increased of C4 grass. This carbon is mainly sequestered in the humus of deep soil layers (20–100 cm). Establishing the pasture with a mixture of plant species could provide unlimited accumulation of C in the long‐term.